Batteries: Enhanced Electrocatalysis via 3D Graphene Aerogel Engineered with a Silver Nanowire Network for Ultrahigh‐Rate Zinc–Air Batteries (Adv. Funct. Mater. 18/2017). (May 2017) - Hu, Shang; Han, Ting; Lin, Chao; Xiang, Weikai; Zhao, Yonghui; Gao, Peng; Du, Fuping; Li, Xiaopeng; Sun, Yuhan
Abstract : Xiaopeng Li, Yuhan Sun, and co‐workers report on the 3D metallic active phase distribution in a self‐assembled composite graphene aerogel. Unraveled by X‐ray μCT presented in article1700041, the interconnected 3D silver networks hold potential to achieve high oxygen reduction activity and ultra‐high rate performance in Zn‐air batteries.